2023
DOI: 10.3390/en16031144
|View full text |Cite
|
Sign up to set email alerts
|

3D CFD Modelling of Performance of a Vertical Axis Turbine

Abstract: Recently, wind turbine research has switched focus to vertical axis wind turbines due to the extensive research that has been performed on horizontal axis wind turbines and the potential of vertical axis wind turbines in built-up areas. This study aims to analyse the performance of a small-scale hybrid vertical axis wind turbine that can switch from functioning as a Darrieus (lift) turbine to a Savonius (drag) turbine by rotating the blades. The turbine was analysed using 3D computational fluid dynamics (CFD) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Our findings, which demonstrate favorable performance compared to similar investigations on Savonius Drag-Type Vertical Wind Turbines, align well with the literature. Specifically, Gerrie et al [11] reported Cp values ranging from 0.12 to 0.14, Al-Gburi et al [15] reported a range from 0.10 to 0.21, Mohamed et al [21] reported a range from 0.10 to 0.25, Shukla et al [14] reported a range from 0.23 to 0.27, and Alom et al [41] reported a range from 0.11 to 0.33. However, it is crucial to acknowledge that each study involves a unique geometry, conditions, and experimental setups, which can influence the observed outcomes.…”
Section: Validity Of the Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings, which demonstrate favorable performance compared to similar investigations on Savonius Drag-Type Vertical Wind Turbines, align well with the literature. Specifically, Gerrie et al [11] reported Cp values ranging from 0.12 to 0.14, Al-Gburi et al [15] reported a range from 0.10 to 0.21, Mohamed et al [21] reported a range from 0.10 to 0.25, Shukla et al [14] reported a range from 0.23 to 0.27, and Alom et al [41] reported a range from 0.11 to 0.33. However, it is crucial to acknowledge that each study involves a unique geometry, conditions, and experimental setups, which can influence the observed outcomes.…”
Section: Validity Of the Resultsmentioning
confidence: 99%
“…Their study categorized prototypes developed by universities and companies worldwide based on system architecture, highlighting both proven hardware configurations and potential future implementations. Gerrie et al [11] presented recent experimental and computational results for three-bladed Darieus and three-bladed Savonius VAWTs. The computational results demonstrate a significant difference from the experimental results, with an order of magnitude discrepancy.…”
Section: Literature Surveymentioning
confidence: 99%
“…For a single turbine model, the performance was determined, and this was followed by measurement of the wind characteristics including velocities, turbulence intensities, and correlation in the wake flow field. Gerrie et al [38] performed 3D modeling of the performance of a VAWT. They employed Computational Fluid Dynamic (CFD) simulations and verified the results with wind tunnel experiments.…”
Section: (B) Wind Tunnelmentioning
confidence: 99%
“…Especially in urban environments, HAWTs are not a feasible option and thus pave the way for adopting vertical axis wind turbines (VAWTs). VAWTs can operate at much lower wind speeds with high turbulence levels due to their lower startup torque and omnidirectionality [3], making them a suitable and commercially viable option in urban settings [4]. Moreover, their lower cut-in speed allows them to have enhanced aerodynamic performance in non-uniform wind environments where flow restrictions, such as buildings, create further air turbulence [5,6].…”
Section: Introductionmentioning
confidence: 99%